UPAYA PENINGKATKAN MENULIS TEKS EKSPOSISI MENGGUNAKAN METODE DISCOVERY PADA KELAS VIII SMP - Usep Suhendi; Rudi Gunawan; Teti Sobari (IKIP Siliwangi, 2019)
The purpose of this research is to find out the increase in student writing learning outcomes in the exposition text material with the Discovery method in class VIII SMP. The research method used is an experimental method with a quantitative form. Data sources were 25 junior high school students. The data collection tool used is a learning implementation plan (RPP), observation sheet and test sheet. The design that the researchers used was pretest-posttes one group design. Data analysis in general concluded that there was an increase in student writing in the text exposition material with a difference in value of 23. Based on the results of class VIII tests before being treated, the average score was 53. get treatment with an average score of 76. The results of this research can be concluded, by applying the Discovery method can improve students' writing skills in exposition text material